Donut Master / Ahmad Zulhilmi Abd Malek ...[et al.] - Abd Malek, Ahmad Zulhilmi; Mohammad Nizam, Nor Ezzety; Ahmad, Arif Aiman; Mustapha Kamil, Ahmad Imran; Shapie, Muhammad Azri (2016)
Today, bakers still use the traditional way to make the mini donuts. Hence the company aim to facilitate the production of doughnut and this machine can increase the production of mini doughnuts. This machine has many molds to produce large amount of doughnut and also a few different types of mold. This makes the mini doughnuts look more interesting, hence attracting the customer's attention to buy it. Currently, there is no factory that produces machines like ours. This product are suitable for bakers who want to have abnormalities in the production of donuts in their bakery, the machine is also suitable for housewives who want to make their own donuts at home as this machine is portable. We are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decided to make some innovation by implying our creativity and modern element in our mini doughnut maker machine.